On Modelling Communication in Ubiquitous Computing Systems using Algebraic Higher Order Nets - Gottmann, Susann; Nachtigall, Nico; Hoffmann, Kathrin (Electronic Communications of the EASST, 2012)
Ubiquitous computing systems (UCSs) are designed to participate almostimperceptibly in everyday life. To ensure a solid operation, a UCS heavily depends on a reliable and efficient communication between its distributed computing components. Moreover components can join and leave the system at any time.In order to guarantee high quality systems, the use of models is inevitable especiallyat an early stage of the development process where models are the only possibilityto address a system which does not yet exist in reality. Petri nets and graph transformationsystems are established, theoretically well-founded concepts for modellingand analysing complex systems.This paper presents a formal approach for modelling core aspects of the communicationin UCSs by using Algebraic Higher Order Nets with Individual Tokens andgraph transformation. The approach is suitable to cover the different aspects ofcommunication and enables the analysis of specific properties. The approach and itssuitability are illustrated based on a running example. The feasibility of embeddingthe approach in a broader context of modelling is demonstrated in applying it to areal world system: the Living Place Hamburg.